1999
DOI: 10.1038/8767
|View full text |Cite
|
Sign up to set email alerts
|

Inactivating mutations and overexpression of BCL10, a caspase recruitment domain-containing gene, in MALT lymphoma with t(1;14)(p22;q32)

Abstract: Mucosa-associated lymphoid tissue (MALT) lymphomas most frequently involve the gastrointestinal tract and are the most common subset of extranodal non-Hodgkin lymphoma (NHL). Here we describe overexpression of BCL10, a novel apoptotic signalling gene that encodes an amino-terminal caspase recruitment domain (CARD), in MALT lymphomas due to the recurrent t(1;14)(p22;q32). BCL10 cDNAs from t(1;14)-positive MALT tumours contained a variety of mutations, most resulting in truncations either in or carboxy terminal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
303
3
15

Year Published

2000
2000
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 360 publications
(331 citation statements)
references
References 24 publications
10
303
3
15
Order By: Relevance
“…Recent reports, including our work in human colonic epithelial cells, have also established a role for Bcl10 in an inflammatory pathway in non-immune cells, including mouse embryonic kidney cells and hepatocytes [5,8,[20][21][22]. Bcl10 is recognized as a mediator of constitutive activation of NFκB in the MALT lymphomas, in which there is a translocation involving Bcl10 [23][24][25]. The Bcl10 effects appear to be mediated through its interaction with IKKγ (or Nemo), the regulatory component of the IKK signalosome.…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports, including our work in human colonic epithelial cells, have also established a role for Bcl10 in an inflammatory pathway in non-immune cells, including mouse embryonic kidney cells and hepatocytes [5,8,[20][21][22]. Bcl10 is recognized as a mediator of constitutive activation of NFκB in the MALT lymphomas, in which there is a translocation involving Bcl10 [23][24][25]. The Bcl10 effects appear to be mediated through its interaction with IKKγ (or Nemo), the regulatory component of the IKK signalosome.…”
Section: Discussionmentioning
confidence: 99%
“…t(1;14)(p22;q32) results in placement of the BCL10 gene adjacent to the strong immunoglobulin heavy-chain locus transcriptional enhancer, leading to deregulated overexpression of Bcl10 (Willis et al, 1999;Zhang et al, 1999). Similarly, t(14;18)(q32;q21) results in translocation of the MALT1 gene to the immunoglobulin heavy-chain locus and leads to MALT1 overexpression (Murga Penas et al, 2003;Streubel et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies suggest that CBM proteins are involved in lymphoma pathogenesis [30,31,41,110]. Chromosomal translocations, which lead to the overexpression of Bcl10 and MALT1 or generation of API2-MALT1 fusion protein, were found in MALT lymphoma [30,41,43], and the activation of NF-κB by these oncogenic proteins is believed to be one of the hallmarks of MALT lymphoma.…”
Section: The Role Of Cbm Proteins In Lymphomamentioning
confidence: 99%
“…Bcl10 was identified by functional cloning from mucosa-associated lymphoid tissue (MALT) lymphoma cells [30,31] and by bioinformatics approaches as a CARD-containing protein [32][33][34]. Genetic studies using Bcl10-deficient mice have revealed that Bcl10 is an essential component in the T cell receptor (TCR)-and B cell receptor (BCR)-induced NF-κB activation, and functions downstream of PKC [29,35].…”
Section: Cbm Proteins In Antigen Receptor Signalingmentioning
confidence: 99%